2019
DOI: 10.1002/cncr.32077
|View full text |Cite
|
Sign up to set email alerts
|

Family communication and patient distress after germline genetic testing in individuals with pancreatic ductal adenocarcinoma

Abstract: Background Germline genetic testing currently is recommended for patients with pancreatic ductal adenocarcinoma (PDAC). In the current study, the authors assessed how often results are communicated to first‐degree relatives within 3 months and the emotional impact of testing on patients. Methods A total of 148 patients who were newly diagnosed with PDAC and who had undergone testing of 32 cancer susceptibility genes at 3 academic centers were selected; 71% participated. Subjects completed the Multidimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…Our research demonstrates that most patients share their genetic test results with at least one relative, which is consistent with previous literature (Cheung et al, 2010; Peters et al, 2019; Stoffel et al, 2008). Similar to Peters et al (2019), the current study found that patients aged ≤65 years shared their genetic test results with at least one relative at a higher rate than older adults (>65 years), but the difference did not reach significance in either study (Peters et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our research demonstrates that most patients share their genetic test results with at least one relative, which is consistent with previous literature (Cheung et al, 2010; Peters et al, 2019; Stoffel et al, 2008). Similar to Peters et al (2019), the current study found that patients aged ≤65 years shared their genetic test results with at least one relative at a higher rate than older adults (>65 years), but the difference did not reach significance in either study (Peters et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Participants were asked to select which categories of relatives they shared information about their cancer diagnosis and genetic test results with, including first‐, second‐, and third‐degree relatives. The survey items were developed by the study team based on the existing literature and their collective clinical experience as genetic counselors (Balmaña et al, 2004; Bouhnik et al, 2017; Katz et al, 2016; Manchanda et al, 2019; Peters et al, 2019; Stoffel et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although probands may be reluctant to share their GT results due to perceived stigma or lack of understanding, we found that GT results were transmitted to 84% of FDRs. This rate is similar to that reported by Peters et al ,37 who found that among patients with PGAs, GT results were disclosed to 79% of FDRs. In contrast, only 31% of informed FDRs subsequently underwent GT, and there was minimal uptake of cascade testing among second-degree relatives (n=4).…”
Section: Discussionsupporting
confidence: 92%
“…In high‐risk families identified through a proband with PDAC, the surveillance status of at‐risk relatives was unknown 45% of the time, compared with 18% unknown status in families identified through an unaffected proband, highlighting potential communication challenges for this group. A recent study of patients with PDAC who underwent genetic testing found that 57% shared their genetic test results with first‐degree relatives, and that patients not meeting prior genetic testing criteria based on cancer family history were less likely to disclose a positive result (69% vs 93%) 30 . A study of communication between patients with cancer and family members found that more than half of patients identified a different family member as the main communicator of health information in their family, suggesting that assisting cancer patients in identifying and empowering a family health informant may be a useful step to improving communication interventions 31 .…”
Section: Discussionmentioning
confidence: 99%